Flexible micro-supercapacitors prepared using direct-write nanofibers. Issue 19 (16th February 2017) - Shen, Caiwei; Wang, Chun-Ping; Sanghadasa, Mohan; Lin, Liwei
Abstract : A direct-write flexible micro-supercapacitor with high performance was demonstrated using a simple and versatile approach. Abstract : Herein, we demonstrated direct-write flexible micro-supercapacitors prepared by the near-field electrospinning of polypyrrole (PPy) nanofibers on a patterned metal electrode deposited on a flexible polymer substrate. The continuous porous nanofiber network with a pseudocapacitance effect greatly increases the capacitance and facilitates ion transport in the electrodes. The prototype based on the lab-synthesized PPy nanofibers shows a high capacitance of 0.48 mF cm −2 when the total area of both electrodes and electrolyte is considered, and the performance is not affected when it is bent to different extents. The micro-supercapacitors were experimentally proved to be highly flexible with excellent electrochemical performance and cycling stability. Our approach is simple, versatile, and compatible with different substrates for the direct integration of energy storage devices in flexible microsystems.